2020
DOI: 10.1109/taes.2019.2928667
|View full text |Cite
|
Sign up to set email alerts
|

Time Synchronization in Photon-Limited Deep Space Optical Communications

Abstract: Random jitter or offset between the transmitter/receiver clocks is an important parameter that has to be accurately estimated for optimal detection of Pulse Position Modulation (PPM) symbols for high data-rate optical communications. This parameter in general is modeled as an unknown random quantity that depends on the clock drift between the transmitter/receiver clocks, and the random motion between the transmitter and receiver stations. In this paper, we have modeled the time jitter for two scenarios-phase m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Furthermore, the authors in [8] analyze the acquisition performance of an FSO system that employs an array of detectors at the receiver, and they demonstrated that the acquisition performance in terms of mean acquisition time can be significantly enhanced by employing a large number of detectors in the receiver array. In the same vein, the study in [9] considers time synchronization schemes based on an array of detectors, and this study showed that the synchronization performance improves significantly by using an array of detectors at the receiver.…”
Section: L R C /O T P a Background Literature Reviewmentioning
confidence: 93%
“…Furthermore, the authors in [8] analyze the acquisition performance of an FSO system that employs an array of detectors at the receiver, and they demonstrated that the acquisition performance in terms of mean acquisition time can be significantly enhanced by employing a large number of detectors in the receiver array. In the same vein, the study in [9] considers time synchronization schemes based on an array of detectors, and this study showed that the synchronization performance improves significantly by using an array of detectors at the receiver.…”
Section: L R C /O T P a Background Literature Reviewmentioning
confidence: 93%
“…The authors in [7] analyze the probability of error in detail for the joint beam position tracking and symbol detection system, and show that the probability of error of a maximal ratio combining scheme is minimized if the beam is tracked accurately enough in time. The authors in [8] consider time synchronization schemes for a detector array receiver in a photon-counting channel in deep space optical communications. The authors in [9] have considered the communications performance for an array of detectors and discussed the effects of the number of detectors and the beam parameter information on the performance.…”
Section: A Background Literature Reviewmentioning
confidence: 99%
“…Furthermore, the authors in [10] analyze the acquisition performance of an FSO system that employs an array of detectors at the receiver. Finally, the authors in [11] consider time synchronization schemes based on an array of detectors.…”
Section: L R C /O T P a Background Literature Reviewmentioning
confidence: 99%